Feminism and religion : how faiths view women and their rights - Paludi, Michele Antoinette (Santa Barbara : Praeger, an imprint of ABC-CLIO, LLC, 2016)
At a conference in 2013, Gloria Steinem noted that religion is the "biggest problem" facing feminism today. In this insightful volume, a team of researchers, psychologists, and religious leaders led by editors Michele A. Paludi and J. Harold Ellens supply their expertise and informed opinions to examine the problems, spur understanding, and pose solutions to the conflicts between religion and women's rights, thereby advocating a global interest in justice and love for women. Examples of subjects addressed include the pro-life/pro-choice debate, feminism in new age thought, and the complex intersections of religion and feminism combined with gender, race, and ethnicity. The contributed work in this unique single-volume book enables a better understanding of how various religions view women--both traditionally and in the modern context--and how feminist thinking has changed the roles of women in some world religions. Readers will come away with clear ideas about how religious cultures can honor feminist values, such as family-friendly workplace policies, reproductive justice, and pay equity, and will be prepared to engage in conversation and constructive debate regarding how faith and feminism are interrelated today. (Publisher).
Introduction / Michele A. Paludi -- Views from the Bible and Buddhism to the Quran and Taoism. Is faith in the Bible and feminism compatible? / Virginia Ingram -- The goddess-worshipping age : feminist egalitarianism in prehistory and early history / Maija Jespersen -- Feminist perspectives from the Hebrew Bible / Ilona Rashkow -- The Church, woman, leadership, and the body / Silvia Geruza Fernandez Rodriguez -- Feminism re-frames who wrote Hebrew scriptures : 10th-century Tamar, the "master" storyteller / Adrien J. Bledstein -- Women in the Holy Quran / Sayyed Mohsen Fatemi -- Feminism in Hinduism : female deities and their influence on South Asian culture / Divyaben Patel, Katherine Anne E. Scott, Paula K. Lundberg-Love, and Jeannine M. Galusha-Glasscock -- Feminism in Buddhism / Linda Chiang -- Femineity in the gospel of John / Kamila Blesing -- Feminism in the Eastern Orthodox Church / Maria Stoyadinova -- The mystical feminine in Baha'i scriptures / Paula A. Drewek -- Religious philosophy in feminism and feminist action. Martial religion, ravaging warfare, and rape : polytheistic Greek and monotheistic Israelite views / Kathy L. Gaca -- Judaism and feminism / Ilona Rashkow -- A room prepared : women and the mystic experience / Anna Byrne -- The feminine spiritual / Deborah Brock -- Feminism and the pro-life/pro-choice debate / Jennifer Elisa Veninga -- Historical resonances of the feminine in the Brazilian Christian religions / Patricia Nobre -- Faith and feminism : resolving the gender issue through mythology and archetype / Deborah Brock -- Feminist, womanist, and mujerista theologies in conversation / Suzanne M. Coyle -- Confucianism and feminism / Mary Wittbold -- Men are not yang and women are not yin : gender construction in the Tao Te Ching and the I Ching / Maija Jespersen -- American Muslim women and faith-inspired activism / Asma Uddin and Firdaus Arastu -- Special women in the Holy Quran / Sayyed Mohsen Fatemi -- Feminism and the future of religion / J. Harold Ellens.
Includes bibliographical references and index.
Keywords: Women and religion; Women -- Religious aspects; Feminism -- Religious aspects; Women's rights -- Religious aspects